Guillain-Barré syndrome associated with COVID-19: a systematic review (Research, Society and Development, 2021)
SARS-CoV-2 is a virus belonging to the coronavirus family and the causative agent of COVID-19. It was discovered in 2019 in Wuhan City, China, it had worldwide dissemination, generating a series of uncertainties regarding its immunopathology and consequences in a short period of time. Among the studies analyzed, there seems to be a possible relationship of previous COVID-19 infection and development of Guillain-Barré Syndrome (GBS), an acute immune polyradiculoneuropathy. The present study with a protocol registered in Open Science (https://osf.io/qe625) aims to analyze the published literature of the mechanism with which COVID-19 can trigger GBS as a secondary framework. To this do so, the methodology of systematic review was used, with data collection performed from March 16, 2021 to March 28, 2021, using individual search strategies described according to Annex 1 in pubmed and embase databases. Inclusion criteria were: articles describing the mechanism of GBS after confirmed SARS-CoV-2 infection, excluding systematic reviews, narrative reviews, literature reviews or meta-analyses, as well as reports with pediatric, hebiatric, obstetric and geriatric patients were not accepted. The results showed 11 articles describing the mechanisms, of which 2 were cohort studies and 9 case reports, all from infected patients with COVID-19 secondarily manifesting GBS. It is concluded that, despite the sparse literature, SARS-CoV-2 can trigger immunoinflammatory responses that trigger a neurological complication picture of GBS.